PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH PEMBELAJARAN MIKRO JURUSAN PKK FT UNM - LILIS, LILIS; AISYAH, ST.; HUDIAH, ANDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research is a quantitative study with the following objectives: (1) To describe the Blended Learning Model for students of the PKK Department in the Microteaching course at the Faculty of Engineering, UNM; (2) To identify the learning motivation of PKK Department students using the Blended Learning Model in the Microteaching course at the Faculty of Engineering, UNM; (3) To examine the influence of the Blended Learning Model on the learning motivation of PKK Department students in the Microteaching course at the Faculty of Engineering, UNM. This study uses an ex-post facto research design. The research population consists of 101 undergraduate students of Fashion Design, PKK Department, Faculty of Engineering, UNM, from the 2021 cohort. The sample size is 50 students, determined using the Slovin formula. The data collection techniques employed include observation, documentation, and questionnaires (surveys). Data analysis techniques include descriptive analysis and simple regression analysis. The results of the study show that: (1) The description of the blended learning model for students falls into the